Pengaruh Pemberian Kadar Bertingkat Ekstrak Daun Ruku-Ruku Hutan (Ocimum Sp) Terhadap Penyembuhan Luka Sayat Pada Mencit - Abeiasa, M. Saka; Ardika, Eche; Mossfika, Eldya (Jurnal Medisains Kesehatan, 2022)
Wound is a state of loss of continuity of tissue structure. Cut injury is an injury caused by being cut by an instrument sharp objects such as knives, razors, mirrors, and other sharp objects. Rukuruku forest is one of the ingredients of traditional medicine that has many properties as anti-bacterial, anti-inflammatory, anti-cancer, anti-fungal and has the effect of anti-oxidant activity. Rukuruku forest leaves contain flavonoid compounds, tannins, saponins, and essential oils that can speed up the treatment of injuries. The content of essential oils acts as an antibacterial, antimicrobial, antiseptic, anti-inflammatory, antioxidant. This research aims to identify the effect of "Rukuruku Hutan" on cut injuries. This research is experimental in nature with a posttest only control group design. Ethanol extract of the leaves of Rukuruku Hutan was made into 3 concentration alterations (10%, 30%, 50). %). Next, the extract was tested in each experimental group, where there was a control group that was given nothing, treatment group 1, treatment 2 and treatment 3, after which the wound healing skills were compared. The results of the research proved that the treatment was not given anything. - does the injury change gradually decrease. At a concentration of 10%, the injury closes more quickly and the length of the injury continues to decrease, at a concentration of 30% the injury turnover decreases only slightly, whereas at a concentration of 50% the injury only slightly undergoes treatment where the injury widens and does not closed after 8 days of testing. The conclusion of this research is that the leaf extract of the forest ruku-ruku can be effective f in the treatment of cut injuries with an optimum concentration of 10%.